Relationship between seminal plasma arginase activity and semen quality in Saanen bucks - Türk, G; Gür, S; Kandemir, Fm; Sönmez, M (My University, 2011)
This study was conducted to determine the relationship between seminal plasma arginase activity and spermatological parameters in bucks. In this study, 5 ejaculates were collected by artificial vagina from each of 5 Saanen bucks of proven fertility. Spermatological parameters (semen volume, semen pH, mass sperm activity, sperm motility and concentration and percentage abnormal sperm) were evaluated immediately after collection in each ejaculate. After semen collection, samples were centrifuged and stored at ?20 ?C for analysis of the arginase activity. The mean level seminal plasma arginase activity recorded was 0.87±0.12 units/mg protein. There existed a positive correlation between the seminal plasma arginase activity and sperm mass activity (r = 0.548, p < 0.01), sperm motility (r = 0.408, p < 0.05) and sperm concentration (r = 0.793, p < 0.01); However, a negative correlationwasrecorded between seminal plasma arginase activity and the percentage abnormal sperm (r =?0.427, p < 0.05). This study suggests that a significant correlation exists between seminal plasma arginase activity and certain spermatological parameters. Therefore, seminal plasma arginase activity may be used as a biochemical criterion to determine sperm quality in bucks.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Seminal plasma Semen quality Arginase activity Saanen goat